CHALLENGES TO THE CURRICULAR REFORM IN AN UNDERGRADUATE NUTRITION PROGRAMPROGRAM: CASE REPORT - Ester de Queirós Costa; Josiane Roberto Domingues; Luciana Reis Malheiros; Maria de Fátima Barros Jardim (Universidade do Estado do Rio de Janeiro, 2013)
Longitudinal and descriptive study aiming to identify the persistent challenges to the curricular reform in the undergraduate nutrition programprogram at Fluminense Federal University. The professors' evaluations of university disciplines, carried out in 2009 and 2011, were compared. Data were collected through a questionnaire with nine mixed questions following the guidance of the Program Pedagogical ProjectProgram; 23 professors participated in 2009, and 34 in 2011. The subjects whose professors participated in both 2009 and 2011 were selected. The results of 18 questionnaires on "contribution of the discipline to develop skills"; "identification of the teaching-learning method used"; "connection of theory and practice"; "integration among disciplines"; "integration among teaching, research and extension" were discussed. The results of 2009 and 2011 showed an ease for "integration among the subjects", "theory and practice" and "teaching and research activities". Regarding "contribution of the discipline to develop skills": there was an increase from 30% to 56% professorin professors' response, explaining how to better develop them. Professors who "deploy active of teaching-learning methods" reduced from 30% to 11%. Finally, "integrating teaching and extension activities" is still difficult: both in 2009 and 2011, only one professor accomplished it. The challenge to adopt an active of teaching-learning method and develop extension activities remains. We believe the success of curricular reform is conditioned by the participation of all actors involved in this process, because their complexity requires work with professors, students and professionals of the same field to share efforts between people who hold some knowledge and power.